ANTIOXIDANT ACTIVITIES OF VARIOUS SEED EXTRACTS FROM FOUR VARIETIES OF RAMBUTAN (Nephelium lappaceum) USING DPPH AND ABTS ASSAYS - Fidrianny, Irda; Fikayuniar, Lia; Insanu, Muhamad (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: The objectives of this research were to study antioxidant activities from various seed extracts of four varieties of rambutan using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azinobis (3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS) methods and correlation of total flavonoid content (TFC), total phenolic content (TPC), and total carotenoid content (TCC) with inhibitory concentration 50 (IC 50 ) of DPPH and IC Methods: Antioxidant activities, TFC, TPC, and TCC of various seed extracts were performed by ultraviolet -visible spectrophotometry and their correlation with IC 50 of DPPH and IC 50 of ABTS antioxidant activities were analyzed by Pearson's method. Results: Ethanolic seed extract of lebak bulus variety had the lowest IC of DPPH scavenging activity 7 Âµg/ml, while ethyl acetate seed extract of rajah variety had the lowest IC 50 50 of ABTS scavenging activity 7.34 Âµg/ml. The highest TFC, TPC, and TCC were given by ethyl acetate extract of binjai variety, ethanolic extract of rapiah variety, and ethanolic extract of rajah variety, respectively. There were negatively high correlation between TFC, TPC,, TCC in seed extracts of rapiah variety with their IC 50 of DPPH and IC 50 of ABTS scavenging activities. Conclusions: All of ethyl acetate and ethanolic seed extracts of four varieties of rambutan were very strong antioxidant by DPPH and ABTS methods. Flavonoid, phenolic, and carotenoid compound in seed extracts of rapiah variety were contributor in their antioxidant activities by DPPH and ABTS methods. The IC 50 of DPPH and IC 50 of ABTS scavenging activities in seed extracts of lebak bulus, rajah, and rapiah varieties gave linear result. Keywords: Antioxidant, 2,2-diphenyl-1-picrylhydrazyl, 2,2'-azinobis (3-ethyl-benzothiazoline-6-sulfonic acid, Seed, Four varieties, Rambutan, Flavonoid, Phenolic, Carotenoid.